2018
DOI: 10.1038/s41467-018-03037-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-equivalent antigen presenting capabilities of dendritic cells and macrophages in generating brain-infiltrating CD8 + T cell responses

Abstract: The contribution of antigen-presenting cell (APC) types in generating CD8+ T cell responses in the central nervous system (CNS) is not fully defined, limiting the development of vaccines and understanding of immune-mediated neuropathology. Here, we generate a transgenic mouse that enables cell-specific deletion of the H-2Kb MHC class I molecule. By deleting H-2Kb on dendritic cells and macrophages, we compare the effect of each APC in three distinct models of neuroinflammation: picornavirus infection, experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 49 publications
0
41
0
Order By: Relevance
“…Studies in viral infections uncovered a possible interplay between astrocytes and CD8 T cells (Xie and Yang, 2015). Thanks to the above-described mouse model and to a recently published floxed K b system (Malo et al, 2018), it will now be possible to explore the role(s) of MHC I presentation by CNSresident cells in homeostasis and disease. In the case of chronic T. gondii infection, these models may be useful to better understand how brain function is impacted by this widespread parasite.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in viral infections uncovered a possible interplay between astrocytes and CD8 T cells (Xie and Yang, 2015). Thanks to the above-described mouse model and to a recently published floxed K b system (Malo et al, 2018), it will now be possible to explore the role(s) of MHC I presentation by CNSresident cells in homeostasis and disease. In the case of chronic T. gondii infection, these models may be useful to better understand how brain function is impacted by this widespread parasite.…”
Section: Discussionmentioning
confidence: 99%
“…The novel H-2D b cKO transgenic mouse system has laid the groundwork to study the crucial role for DCs and other APC subsets in CD8 T cell priming against CNS pathogens without disrupting other functions of these cell types, such as CD4 T cell priming or cytokine secretion. The presently described H-2D b cKO mouse, in conjunction with our previously published H-2K b cKO mouse, enables assessment of antigen presentation in disease models [49]. Here, we have articulated the requirement for CD11c+ cells in priming acute CD8 T cell responses against intracranial infection by the picornavirus TMEV and shown that LysM+ APCs play a subordinate role in this process.…”
Section: Discussionmentioning
confidence: 95%
“…A study conducted by our research program in parallel to the one currently presented, utilizing the LysM-cre system in K b LoxP transgenic animals, had similar results in regards to the relative importance of MΦs in CD8 T cell priming. Conditional depletion of H-2K b based antigen presentation ability in MΦs resulted in no defect in the priming of CD8 T cells at 7 dpi against the K b :OVA epitope, which served as the immunodominant epitope in the engineered OVA-TMEV [49]. Again, similar to what has been put forward in regards to the present study utilizing the D b allele and a natural viral epitope, it is possible that the contribution of any potential MΦ populations to priming this antiviral CD8 T cell response are minimal in comparison with those of CD11c+ cells and are therefore masked as long as DCs remain antigen presentation competent [49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations